The smaller arachnid orders: diversity, descriptions and distributions from Linnaeus to the present (1758 to 2007)* - Harvey, Mark S. (Zootaxa, 2007)
Carolus Linnaeus’ contribution to the study of the smaller arachnid orders was modest with the description of four taxa: the pseudoscorpions Acarus cancroides and A. scorpioides, the whip scorpion Phalangium caudatum, and the whip spider P. reniforme. Since then, more than 5,100 species have been named in eight orders by a plethora of researchers. Trends in species descriptions over time are explored; the presence of different accumulation curves for some orders is thought to be due to advances in the study of morphology combined with a greater focus on collecting small arachnids in tropical ecoregions. Pseudoscorpion species richness is examined against log-transformed area data for all countries of the world. Anomalies, such as the poor representation of pseudoscorpion diversity in some large countries such as China, appear to be due to a low number of active researchers.